Effect of Tooth Paste and Mouth Wash on Brackets Dimension - Saba H Al-Zubaidi (University of Mosul, College of Dentistry, 2010)
Aims: To evaluate whether dimensions of the brackets change due to corrosion when immersed in tooth paste and mouth wash at different intervals of immersion (1, 14 and 30 days). Materials and Methods: Three groups of bracket (ten for each), the first group is the control group. The second group immersed in tooth paste (Anber- Iraq) for one minute three times daily then removed and washed in distill water, dried and be ready for testing nine dimensions of the bracket at three intervals (1, 14, and 30 days). The same procedure was repeated for the third group that was immersed in mouth wash (chlorhexidine). The data was analyzed using Descriptive statistic, analysis of variance (ANOVA) at p≤0.05. These data were then analyzed by the Duncan multiple analysis range test to locate the signifi-cant differences among the groups. Results: The bracket base length showed a significant difference among the control and the immersed brackets in mouth wash. The bracket base length, wing length and wing width showed a significant differences among the control and the immersed brackets in tooth paste. Conclusions: when immersing the brackets in tooth paste and mouth wash no significant dimen-sional changes occurred in bracket's dimension except for the bracket base length of the brackets im-mersed in mouth wash and the bracket base length, wing length and width of brackets immersed in tooth paste that showed significant changes among the groups.